Vibration level reduction by floor coverings installed on wooden slabs. Issue 2 (June 2022) - Lietzén, Jesse; Kylliäinen, Mikko; Valjakka, Saveli; Pajunen, Sami
Effect of floor coverings on impact sound insulation can be described with a vibration level reduction (Δ La ). In this study, tests with two floor coverings, eight wooden slabs and with a concrete mock-up slab were conducted by applying the method presented by Sommerfeld and the standard ISO 16251-1. The aim was to study the differences affecting the measured Δ La and the behaviour of the floor coverings installed on different slabs. The results suggest that the Δ La on concrete slabs do not correspond with the Δ La on wooden slabs. Thus, the floor coverings should be measured on wooden slabs when they are to be used within the timber construction industry. The results also show that the coverings should be measured on the wooden slabs where the products are expected to be used. In addition, a standardized test method for the wooden slabs corresponding the method of ISO 16251-1 should be developed.